In situ synthesized SrF2/polyvinylidene fluoride nanocomposite film based photo-power cell with imperious performance and stability. (20th August 2018) - Khatun, Farha; Thakur, Pradip; Hoque, Nur Amin; Kool, Arpan; Roy, Swagata; Biswas, Prosenjit; Bagchi, Biswajoy; Das, Sukhen
Abstract: A self-charged photo-power cell, named as light sensitive energy storage device has been developed in a simplified way for application as a portable photo-charged power bank. The Photo-Power Cell is fabricated by assembling a photoelectrode (FTO) involving a dye-sensitized solar part as photo-electrons generator, combined with the electroactive and high dielectric SrF2 -PVDFNCfilm as storage unit. Electroactive β phase crystallization and large interfacial polarization between the SrF2 NPs and poly (vinylidene fluoride) matrix result in high dielectric value ∼ 5141 of the nanocomposite film. The device is charged by up to 1.48 V under visible light illumination (∼110 mW/cm 2 ) with a constant discharge current density ∼1.64 mA/cm 2 . The photogenerated charge and power density of the photo-power cell are found to be ∼24.3 W/m 2 and 2400 C/m 2 respectively. Our photo-power cell shows maximum areal specific capacitance ∼1600 F/m 2 with 92% energy storage efficiency. The achieved overall efficiency (%) is found ∼ 2.57. The charging-discharging stability is also tested for a long time span of 12 weeks. The efficacy and durability of our fabricated device has also been demonstrated by glowing up 24 commercially available blue light emitting diodes for 10 days with same intensity by charging one time under light. Graphical abstract: Image 1 Highlights: Synthesis of electroactive and high dielectric SrF2 -PVDF nanocomposite film via in situ process. Fabrication of a simplistic SrF2 -PVDF film based self-charged photo-power cell. The power cell exhibits a remarkable storage efficiency ∼92%. The device shows maximum areal specific capacitance ∼1600 F/m 2 . The hybrid device is able to lightening 24 LEDs for 10 days with same intensity.